Promising Blockchain Technology Applications and Use Case Designs for the Identification of Multinational Victims of Mass Disasters - Alsalamah, Shada; Nuzzolese, Emilio (Frontiers in Blockchain, 2020)
In mass disasters with multinational victims, it is critical to identify the deceased for judicial, ethical, religious and human rights reasons, as well as to allow the next of kin to complete the grieving process. Disaster Victim Identification (DVI) process is a complex procedure where Post-mortem (PM) identifying data, essentially fingerprints, DNA and dental, is collected in order to be compared with equivalent Antemortem (AM) data related to the missing persons list. Although there are solutions used in the field of human identification, they all fall short of equipping them with the tools needed for achieving human identification in a timely manner. Initially, it is significantly challenging to manage missing person lists containing years, and sometimes decades, of family AM data resources’ updates. Furthermore, there is currently no record of any holistic technical solutions for managing both AM and PM for human identification to support collaborative multinational and interjurisdictional processes. Blockchain technology provides the tools to facilitate building trustworthy, secure and holistic ecosystems, and it can disseminate siloed AM and PM data across systems, protecting data breaches, redundancies, inconsistencies, and errors. As such, blockchain technology can revolutionize the human identification process worldwide in terms of managing missing person lists, AM data repositories for living people, PM data repositories of recovered unidentified victims, and contribute to the comparison of compatible biological profiles for definitive identification. Using real-world scenarios, the authors propose a number of promising use cases to attain a holistic understanding of the challenges, and present how blockchain technology meets such challenges and facilitates multi-jurisdictional data information-sharing in conjunction with the forthcoming circulation of patients’ electronic medical and dental records.